Boss of Busy : Combat Burn Out and Get Clear on What Matters. - Hill, Alison (John Wiley & Sons, Incorporated, 2019)
Bring calm to the chaos in your life. Whether you find yourself checked out, burnt out, or just plain freaked out; you deserve better. Psychologist Alison Hill takes you deep into the key pillars for our happiness, health and sanity to help you live a life filled with purpose and progress. Productivity training or the latest organisational system will only take you so far. To make lasting change you need the right tools, mindset and skills. Boss of Busy helps you find the courage and optimism to live the life you crave, let go of what is holding you back and learn how to prioritise what really matters. Originally published in 2016 as Stand Out , this book has been reviewed and redesigned to become part of the Wiley Be Your Best series - aimed at helping readers acheive professional and personal success.